6-Bromoindirubin-3′-oxime derivatives are highly active colistin adjuvants against Klebsiella pneumoniae. Issue 2 (14th December 2022) - Li, Haoting; Mattingly, Anne E.; Smith, Richard D.; Melander, Roberta J.; Ernst, Robert K.; Melander, Christian
Abstract : Multidrug resistant (MDR) bacterial infections have become increasingly common, leading clinicians to rely on last-resort antibiotics such as colistin. Abstract : Multidrug resistant (MDR) bacterial infections have become increasingly common, leading clinicians to rely on last-resort antibiotics such as colistin. However, the utility of colistin is becoming increasingly compromised as a result of increasing polymyxin resistance. Recently we discovered that derivatives of the eukaryotic kinase inhibitor meridianin D abrogate colistin resistance in several Gram-negative species. A subsequent screen of three commercial kinase inhibitor libraries led to the identification of several scaffolds that potentiate colistin activity, including 6-bromoindirubin-3′-oxime, which potently suppresses colistin resistance in Klebsiella pneumoniae . Herein we report the activity of a library of 6-bromoindirubin-3′-oxime analogs and identify four derivatives that show equal or increased colistin potentiation activity compared to the parent compound.